(7x + 3)(4x + 2) = 28x2 - 15
=> 7x(4x + 2) + 3(4x + 2) = 28x2 - 15
=> 28x2 + 14x + 12x + 6 - 28x2 + 15 = 0
=> (28x2 - 28x2) + (14x + 12x) + (6 + 15) = 0
=> 26x + 21 = 0
=> 26x = -21
=> x = -21/26
\(28x^2+14x+12x+6=28x^2-15\)
\(26x+6=-15\)
\(26x=-21\)
\(x=-\frac{21}{26}\)
( 7x + 3 )( 4x + 2 ) = 28x2 - 15
<=> 28x2 + 26x + 6 = 28x2 - 15
<=> 28x2 + 26x - 28x2 = -15 - 6
<=> 26x = -21
<=> x = -21/26
\(\left(7x+3\right)\left(4x+2\right)=28x^2-15\)
\(28x^2+14x+12x+6=28x^2-15\)
\(28x^2+14x+12x+6-28x^2+15=0\)
\(26x+21=0\)
\(26x=-21\)
\(x=-\frac{21}{26}\)